Intergroup rudeness and the metapragmatics of its negotiation in online discussion fora - Kleinke, Sonja; Bös, Birte (Pragmatics, 2015)
This study investigates the communicative practices in English and German online discussion fora as exemplified by two thematically related sample threads. Combining first- and second-order approaches to (im-)politeness, the paper focuses on the question of how participants use intergroup rudeness as a means of in- and outgroup construction and examines how intergroup rudeness is metapragmatically negotiated as the discussions unfold. The results show that intergroup rudeness as well as metapragmatic comments are handled very differently in the two communities explored. Suggesting cultural preferences, there is a much higher degree of interactivity and a clear preference for negotiation at an interpersonal level in the German discussion group; its English counterpart favours negotiation at an intergroup level. Both threads provide metapragmatic evidence that the frequent use of rudeness tokens does not automatically make rudeness an accepted norm.